Relationship of Complete Basic Immunization Status to Acute Respiratory Tract Infection In Toddlers In the Tilango Health Center Working Area - Wahyuni Saputri Hudjuala; Ridha Hafid; Cindy Puspita Sari Haji Jafar (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Acute Respiratory Tract Infection is one of the main causes of pain and death in toddlers. The World Health Organization states that this disease is the second cause of death for children under five globally. In Indonesia, especially Gorontalo Province, Acute Respiratory Tract Infection in toddlers is still relatively high, with Gorontalo Regency as the area with the highest number of cases, especially in Tilango. One of the prevention efforts is the provision of complete basic immunization to increase immunity to diseases. This study aims to determine the relationship between complete basic immunization status and Acute Respiratory Tract Infection in toddlers in the working area of the Tilango Health Center. This study is a quantitative research with an analytical observational design using a cross sectional approach. The population of this study was all toddlers with a sample of 92 toddlers using purposive sampling techniques. The research instrument uses checklist sheets. Data analysis with univariate and bivariate using the Chi-Square test. The results showed that there was a relationship between complete basic immunization status and Acute Respiratory Tract Infection in toddlers (p-value < 0.05). Toddlers with incomplete basic immunization status are more likely to experience infections than toddlers with complete basic immunization status. In conclusion, there is a relationship between complete basic immunization status and Acute Respiratory Tract Infection in toddlers. It is recommended to health workers to increase education and complete basic immunization coverage as a preventive measure.